Scheduling collective communications on wormhole fat cubes - Dvorak, V. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
A recent renewed interest in hypercube interconnection network has been concentrated to the more scalable and mostly cheaper version known as a fat cube. This paper generalizes the known results on time complexity of collective communications on a hypercube for the wormhole fat cube. Examples of particular communication algorithms on the 2D-fat cube topology with 8 processors are summarized and given in detail. The performed study shows that a large variety of fat cubes can provide lower cost, better scalability and manufacturability without compromising communication performance.